A case of postpartum headache post dural puncture. Post Dural Puncture Headache or Reversible Cerebral Vasoconstriction Syndrome - Posterior Reversible Encephalopathy Syndrome? - Turetti, Melania; Barbagallo, Maria; Scoditti, Umberto; Genovese, Antonio; Angeli, Laura; Fieni, Stefania; Frusca, Tiziana; Bignami, Elena Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Reversible Cerebral Vasoconstriction Syndrome (RCVS) and Posterior Reversible Encephalopathy Syndrome (PRES) are two rare neurological conditions, clinically characterized by headache. In our case a diagnosis of PDPH was made though imaging showed signs of RCVS-PRES. We present a case of RCVS-PRES in a postpartum woman who presented headache as first symptom and only later experienced seizures. Dural puncture worked as a confounding factor in the clinical postpartum evaluation. We want to focus the attention on changes of clinical characteristics of headache as an important factor to be analysed, in order to have a prompt diagnosis. We therefore propose a diagnostic algorithm. Moreover, we evaluate possible triggers of RCVS and PRES; in our case dural puncture is probably not the trigger, in fact there were no liquoral hypotension signs on imaging.